Sistem Pemilihan Produk Terlaris Seller Flanelade dengan Metode MAUT - Ade Rizka; Annisa Fadillah Siregar; Farid Akbar Siregar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Online and offline buying and selling transactions require evaluation so that they can continue to grow. Products that have been sold have various categories, so the turnover of each product is different. This becomes the basis for evaluating future business strategies. However, turnover information for each product that is still processed manually will result in various risks such as inaccurate data, inaccurate calculation of category criteria, and inefficient time. The MAUT method is used in this research process because the calculation of the best-selling product category based on sales requires an appropriate and appropriate method. The criteria used in the calculation include price, sales, returns, and product evaluation. The results of the research on the MAUT method with 10 sample data on pillowcase products based on the color and pattern of the fabric that match the criteria can help calculate the highest turnover and produce alternative best-selling products. The product alternative with the highest final utility value, namely 0.308, is categorized as the best-selling product and has the highest sales turnover within 1 year. The calculation system is capable of processing the maximum amount of product data efficiently and quickly, so there are no obstacles such as manual calculations